Gut microbiota‐derived lipopolysaccharide uptake and trafficking to adipose tissue: implications for inflammation and obesity. (29th December 2015) - Hersoug, L. ‐G.; Møller, P.; Loft, S.
Summary: The composition of the gut microbiota and excessive ingestion of high‐fat diets (HFD) are considered to be important factors for development of obesity. In this review we describe a coherent mechanism of action for the development of obesity, which involves the composition of gut microbiota, HFD, low‐grade inflammation, expression of fat translocase and scavenger receptor CD36, and the scavenger receptor class B type 1 (SR‐BI). SR‐BI binds to both lipids and lipopolysaccharide (LPS) from Gram‐negative bacteria, which may promote incorporation of LPS in chylomicrons (CMs). These CMs are transported via lymph to the circulation, where LPS is transferred to other lipoproteins by translocases, preferentially to HDL. LPS increases the SR‐BI binding, transcytosis of lipoproteins over the endothelial barrier, and endocytosis in adipocytes. Especially large size adipocytes with high metabolic activity absorb LPS‐rich lipoproteins. In addition, macrophages in adipose tissue internalize LPS‐lipoproteins. This may contribute to the polarization from M2 to M1 phenotype, which is a consequence of increased LPS delivery into the tissue during hypertrophy. In conclusion, evidence suggests that LPS is involved in the development of obesity as a direct targeting molecule for lipid delivery and storage in adipose tissue.